Yoga and Eating Disorders: Can Mindful Movement Restore Balance? - Katarzyna Agopsowicz; Katarzyna Blicharz; Michalina Piwowar; Martyna Biernacka; Igor Biernacki (Quality in Sport)
Eating disorders constitute a significant mental health issue, marked by serious disruptions in eating behaviors, body image concerns, and self-perception struggles. Individuals affected frequently endure substantial psychological and physical impacts, highlighting the need for comprehensive, multi-faceted treatment approaches. This article investigates yoga as an adjunctive therapeutic practice, focusing on mindful movement's capacity to enhance self-awareness, emotional stability, and promote a healthier relationship with one's body.